Decency Norms in Law Enforcement to Online Prostitution in Indonesia: An Islamic Law Perspective - Alfitra, Alfitra; Faizin, Afwan; Mansur, Ali; Zuhdi, Muhammad Harfin (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This study aims to describe Islamic law norms as living Law are offered decency norms for law enforcers against online prostitution as Article 27 of Information and Electronic Transaction (IET) law, and the factors that prevent the enforcement of the decency norms under Article 27 against the massive development of online prostitution. This research was conducted in four provinces: Jakarta, West Java, East Java, and South Sulawesi. The interviewees are investigators from the Indonesian National Police and District Court judges in four cities of four provinces. The method used is a qualitative approach.The research subjects were selected by purposive sampling,Â  and the data were analysed using descriptive analysis. The findings of this study show Islamic Law as decency norms or living law can be a priority for law enforcement to online prostitution by using Article 27 of the IET Law, where decency norms can be imposed on perpetrators, pimps, sex workers, and buyers. Sex services, as well as intermediaries. This study also shows the reluctance of law enforcers at the investigation and court levels to enforce Article 27 more strictly and maximally because it is not a cybercrime priority that must be enforced to prevent the massive development of online prostitution.